Elaboración de la agenda provincial de reducción de riesgos y cambio climático. Caso: Gobierno Provincial de Tungurahua periodo mayo – septiembre 2023. - Báez Moya, Jorge Fernando (2024)
The geographic area of Tungurahua has been identified as a region susceptible to threats both natural and caused by human activities, and unfortunately, it does not have the assistance required to deal with these events efficiently. Within the present case study carried out in the GPT (Provincial Government of Tungurahua), it was possible to identify the current situation of vulnerability in which the province of Tungurahua finds itself in relation to dangerous events and climate change, as well as to develop the Provincial Agenda for Risk Reduction and Climate Change, which was created using the Methodology for the Formulation of Risk Reduction Agendas prepared by the Secretary of Risk Management, which is focused with variables, indicators and weightings. It can be mentioned that the province of Tungurahua has a high vulnerability to the occurrence of dangerous events, both of natural origin and caused by climate change, when preparing the Provincial Agenda for Risk Reduction and Climate Change it will greatly favor the province to mitigate the negative effects that the occurrence of dangerous events would produce, achieving inter-institutional coordination between the cantonal GADs and the HGPT. Palabras Claves o Descriptores en español y en inglés Debe escribir 4 palabras claves relacionadas con el contenido del Trabajo de Titulación en mayúsculas. KEYWORDS: THREATS, RISK MANAGEMENT, REHABILITATION, RECONSTRUCTION, MITIGATION, RISK REDUCTION.